Solve for where:
If your solution set is of the form , find .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let f ( x ) = ∣ x 2 − 1 ∣ + ∣ x 2 − 4 ∣ , which is an even function. Therefore, we need only to consider for x ≥ 0 and reflect the solutions in x ≤ 0 . There are three cases to be considered.
For 0 ≤ x < 1 ,
f ( x ) 5 − 2 x 2 ⟹ x = 1 − x 2 + 4 − x 2 = 5 − 2 x 2 > 3 < 1
For 1 ≤ x < 2 , f ( x ) = x 2 − 1 + 4 − x 2 = 3 < 3
For x ≥ 2 ,
f ( x ) 2 x 2 − 5 ⟹ x = x 2 − 1 + x 2 − 4 = 2 x 2 − 5 > 3 > 2
Reflecting the solutions in x ≤ 0 , we have ∣ x 2 − 1 ∣ + ∣ x 2 − 4 ∣ > 3 , for x ∈ ( − ∞ , − 2 ) ∪ ( − 1 , 1 ) ∪ ( 2 , ∞ ) . ⟹ ∣ a ∣ + ∣ c ∣ + d + e = ∣ − 2 ∣ + ∣ − 1 ∣ + 1 + 2 = 6